Strategi Komunikasi Pemasaran dalam Meningkatkan Penjualan Produk Edamame di PT. Mitratani Dua Tujuh Kabupaten Jember - Dian Oktavia Edita Putri (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Marketing communication refers to a company's effort to convey information, influence, and remind consumers both directly and indirectly regarding the products offered. In marketing communication, information is conveyed through a promotion mix that includes advertising, sales promotion, personal selling, direct marketing, and public relations. This research was conducted to analyze the marketing communication strategies implemented by PT Mitratani Dua Tujuh in increasing sales of edamame products, both in the domestic and export markets. The theory used to analyze the marketing communication strategy at PT. Mitratani Dua Tujuh is the promotion mix, as proposed by Haque-fawzi et al. (2022). The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The selection of informants was conducted using a purposive sampling technique. The informants in this study consisted of internal company parties (marketing and digital marketing teams), distributors, consumers, and a competitor. The results show that the marketing communication strategy is implemented through five elements of the promotion mix: Advertising is carried out through social media with paid advertisement using Meta Ads; Sales promotion is conducted by offering promotions on market place platforms, bundling products, and discount systems based on cold storage stock; Personal selling is done through distributors, direct interactions with consumers at exhibitions, participation in ITPC, and offering products to intermediary services; Direct marketing is done through intense visits, product presentations, and price quotes to distributors and international buyers; and Public relations are carried out by participating in local and international events, providing sponsorships, and implementing CSR programs. In general, these strategies have been implemented as planned, although several obstacles remain, such as budget limitations, lack of variety in promotional content, and limited international communication. The marketing communication strategy has proven effective in increasing the sales of edamame products. However, it is necessary to improve the quality of digital content, enhance responsiveness to consumers, provide international communication training, and expand collaboration with market place platforms to optimize the achievement of the company's marketing goals.
Reaploud Repository February 2026_Hasyim
Keywords: Marketing Communication; Promotion Mix; Sales Increase; Edamame Products.